Nickel-Doped Tungsten Disulfide for Energy Storage Applications - Pandey, Keshab; Jeong, Hae Kyung (Journal of Nepal Physical Society, 2023)
Nickel-doped hexagonal pyramid-like tungsten disulfide (WS2) has been synthesized via a simple hydrothermal synthesis method and offers great promise for use in electrochemical energy storage devices such as supercapacitors. The nickel concentration of 3, 4.5, and 6 at. % was added to WS2. Three-electrode and two-electrode configurations are used to test the electrochemical performances of the materials as prepared. The nickel doping of 4.5 at. % exhibits a high specific capacitance of 144 F g−1 at a current density of 1 A g−1 with an energy density of 13.3 Wh kg−1 and power density of 802 W kg−1 for the symmetric supercapacitor device. Increased electrochemically active surface area and decreased impedance are attributed to the improved supercapacitive performances. Finally, high specific power retention (92.1%) and Coulomb efficiency (86.0%) were demonstrated after 3,000 cycles. These results demonstrate that the synthesized nickel-doped WS2 can be used for high-performance supercapacitor flexible electrodes.